Correlations between gut microbiota and lichen planus: a two-sample Mendelian randomization study - Yan, Ming; Ouyang, Yu-Long; Xiao, Li-Yuan; Ao, Man; Gosau, Martin; Friedrich, Reinhard E.; Smeets, Ralf; Fu, Ling-Ling; Feng, Hong-chao; Burg, Simon (Frontiers in Immunology, 2023)
Purpose Several existing studies have revealed that the occurrence of lichen planus (LP) is relevant to the gut microbiota, and the causal relationship between gut microbiota and LP was analyzed using the Mendelian randomization (MR) method. Methods Through the two-sample MR method, single nucleotide polymorphisms (SNPs) relevant to gut microbiota were selected as instrument variables (IVs) to evaluate the causal association between gut microbiota and the risk of LP. Results According to the selection criteria of inverse-variance weighted (IVW), six bacterial genera were found to be significantly linked to the initiation of LP; The IVW results suggested that Oxalobacteraceae, Victivallaceae, and Actinobacteria could restrain the initiation of LP, showing protective effects against LP. Desulfovibrio, Veillonella, and Ruminococcus gauvreauii groups were demonstrated to have casual correlations with the onset of LP. Conclusion The relationship between gut microbiota and LP was not a single positive or inverse relationship. Investigation of the causal relationship of these gut microbiota with LP could further provide evidence for the intestine-skin axis theory. However, the specific mechanism of microorganisms affecting the skin remains to be clarified. In this paper, the protective effects and mechanisms of Oxalobacteraceae, Victivallaceae, and Actinobacteria on LP require further exploration.